Global Landmarks of Digital Citizenship in the Conditions of Today's Globalization Challenges - Lomachinska, Irina; Volynets, Irina (Educological discourse, 2024)
The article is devoted to the analysis of digital citizenship as an effective strategy for the development of worldview orientations of student youth in the modern digital age. The main methods of scientific research are structural, comparative, analysis, synthesis, generalization and the method of collecting sociological information. Digital citizenship is presented as a worldview based on safety, morality, legality, responsibility and intellectual honesty. The key parameters of digital citizenship are determined - digital literacy, digital etiquette, digital rights and responsibilities, digital health, digital security, digital communication, digital commerce, digital access, and their essential features are clarified. It is noted that safety and well-being in the digital age defines the ability to counter the risks that the digital world can bring in order to protect one's physical and mental well-being. Accordingly, digital citizenship should be understood as a way to prepare the younger generation for active participation in society and in serving the nation's interests in the digital environment. The main features of today's youth as the Internet generation are outlined - highly ambitious, realistic, critical, self-confident. Thanks to the ability to quickly search for information, representatives of the Internet generation are more knowledgeable and informed about the events and phenomena of the surrounding world. The representatives of the Internet generation choose social networks as the preferred resource for communication, which they use not only to search for information or communicate, but also for active self-presentation of their own social position. Taking into account the international experience of scientific research, digital citizenship not only provides opportunities for safer moral-ethical and socio-legal functioning in the digital environment in the face of global challenges of the modern digital age, but also forms the worldview foundations of the formation of a conscious and socially responsible personality with an active civic position capable of influencing social and political processes. Digital citizenship ensures the effective integration of young people into the digital social space, therefore there is a need to study the basic principles of digital citizenship in higher education institutions of Ukraine